Analisis variasi suhu 150°C, 160°C, 170°C dalam variasi jumlah tumbukan terhadap spesifikasi Asphalt Concrete Binder Course (AC-BC) - Yani, Lusi; Rahmaniah, Rahmaniah; Asriani, Asriani (Teknosains: Media Informasi Sains dan Teknologi, 2023)
Asphalt Concrete Binder Course (AC-BC) is a type of pavement on roads that has a cover layer with an asphalt aggregate mixture structure. The AC-BC layer functions to maintain resilience and stability on roads resulting from the effects of weather and vehicle loads. The aim is to determine the effect of pure asphalt on the specifications of the Asphal Concrete Binder Course (AC-BC), to determine the effect of temperature variations and collisions on the specifications of the Asphal Concrete Binder Course (AC-BC), and to determine the effect of the composition of the asphalt mixture on the specifications of the Asphal Concrete Binder Course ( AC-BC). From the 5 tests of asphalt, a penetration value of 62.6 mm, a melting point of 50 oC, a ductility value of 150 cm, an asphalt mass of 1.0618 gr, and a loss of asphalt mass of 0.36%. The test results identified that the AC-BC asphalt used complied with SNI 06-2456-1991 and SNI 2432-2011 standards. The marshall characteristic values for each asphalt content with temperature variations of 150 oC, 160 oC and 170 oC obtained from the test results met the 2018 Bina Marga specifications, with the ideal mixing temperature at 150 oC and 160 oC. The marshall characteristic value indicates that the mixing composition can increase the ability of the pavement, where a high temperature increase will cause the mixed material to overheat and burn so that it is easily deformed, unstable, and bleeding will occur. The effect of temperature changes can reduce stability and reduce performance on AC-BC concrete pavements. Compaction when mixing asphalt identifies air voids and stability values according to SNI with the ideal number of collisions, namely 75 and 80 collisions.